Development of extruded puffed corn-fish snack from silver carp (Hypophthalmicthys molitrix) - Shahmohammadi, Hamidreza (2013)
Corn-based snacks are generally well accepted but low in protein content due to the limited protein–based ingredient incorporated in the formulations. This is because the common extrusion technology used to produce the snack is basically developed for starch-based dough formulation. Incorporating fish protein in the formulation could result in several problems relating to extrusion condition, textural properties and the stability of the snack itself. Therefore, in order to overcome these constraints, the present study was aimed at developing a nutritious puffed corn-fish snack by (i) enhancing the nutrition value and texture of the snack (ii) optimizing the extrusion conditions for enhanced textural properties (iii) and evaluating the storage stability of the developed snack. Extruded puffed corn-fish snack was produced from corn grits containing 0 to 30% of Silver carp (Hypophthalmicthys molitrix). This was followed by optimizing the composition of the snack using Response Surface Methodology. The optimum formulation was obtained at 85% corn and 15% fish. Improvement of textural characteristics of the puffed corn-fish snack was studied by nucleating materials (calcium carbonate, magnesium silicate, sodium bi-carbonate and bran) which were incorporated at 1 to 2% for the first three nucleating agents and at 5 and 10% for bran. The results showed that all nucleating agents significantly enhanced the texture of the puffed snack except for bran. Among the four studied nucleating agents, magnesium silicate at 0.5% was the best texture modifier. Microstructure of the puffed corn-fish snack, which was examined by Scanning Electron Microscope showed that the air cell diameter in the snack which containing 0.5% of magnesium silicate was reduced 7.32 times while the number of cells per unit area was increased 4.76 times compared to the control. In order to optimize the extrusion conditions, RSM experimental design was performed. The optimum extrusion condition was determined to be at 116ºC, 1107 g/min feed rate and 148 rpm screw speed. Storage stability of the developed snack both unseasoned and seasoned packed in Biaxillary Poly Propylene films were studied over a storage period of 30 weeks. Microbial conditions were evaluated at 0, 15 and 30 weeks of storage while chemical and sensory parameters were carried out at six weeks intervals for 30 weeks. It is concluded that the shelf-stable, nutritious crispy puffed corn-fish snack containing 15% fish, 84.5% corn and 0.5% magnesium silicate (w/w) can be produced, packed under air atmosphere conditions with metalized BOPP and well accepted for a storage period of 28 weeks.